2001
DOI: 10.3758/bf03195349
|View full text |Cite
|
Sign up to set email alerts
|

Age of acquisition and imageability ratings for a large set of words, including verbs and function words

Abstract: Age of acquisition and imageability ratings were collected for 2,645 words, including 892 verbs and 213 function words. Words that were ambiguous as to grammatical category were disambiguated: Verbs were shown in their infinitival form, and nouns (where appropriate) were preceded by the indefinite article (such as to crack and a crack). Subjects were speakers of British English selected from a wide age range, so that differences in the responses across age groups could be compared. Within the subset of early a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
308
9
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(357 citation statements)
references
References 45 publications
30
308
9
6
Order By: Relevance
“…Because, on average, nouns and especially object nouns of the sort studied in our literature, fall at the more concrete end of the SICI continuum than do verbs. These more imageable words are learned earlier than less imageable words, regardless of syntactic class (Bird, Franklin, & Howard, 2001). Preliminary data in our labs (Lannon et al, in preparation) suggests that adult ratings of imageability correlate with age of acquisition on standardized material checklists, like the MacArthur Communicative Inventory (Fenson et al, 1994) irrespective of word class in both English and Chinese.…”
Section: How the Ecm In Combination With The Sici Continuum Helps Umentioning
confidence: 95%
See 3 more Smart Citations
“…Because, on average, nouns and especially object nouns of the sort studied in our literature, fall at the more concrete end of the SICI continuum than do verbs. These more imageable words are learned earlier than less imageable words, regardless of syntactic class (Bird, Franklin, & Howard, 2001). Preliminary data in our labs (Lannon et al, in preparation) suggests that adult ratings of imageability correlate with age of acquisition on standardized material checklists, like the MacArthur Communicative Inventory (Fenson et al, 1994) irrespective of word class in both English and Chinese.…”
Section: How the Ecm In Combination With The Sici Continuum Helps Umentioning
confidence: 95%
“…Bird et al (2001) found that regardless of grammatical category (including verbs and function words), age of acquisition is significantly correlated with imageability. Further, imageability can predict the ease with which one can determine the referent of a novel word in context.…”
Section: Sici: C Is For Concreteness and I Is For Imageability The Cmentioning
confidence: 96%
See 2 more Smart Citations
“…The sets were also matched on imageability. Imageability ratings were taken from the MRC lexical database (Wilson, 1988) (www.psy.uwa.edu.au/mrcdatabasewa _ mrc.htm) and from norms published by Bird et al (2001) and Cortese and Fugett (2004). Imageability ratings for the study items ranged from 140 to 659 (mean = 458, SD = 125) and were uncorrelated with letter length, phoneme length, mean positional bigram frequency, orthographic neighborhood count, or word frequency.…”
Section: Stimuli and Taskmentioning
confidence: 99%